Exhibiting Atrocity: Memorial Museums and the Politics of Past Violence - Sodaro, Amy (Rutgers University Press, 2018)
Through a global comparative approach, Amy Sodaro uses in-depth case studies of five exemplary memorial museums that commemorate a range of violent pasts and allow for a chronological and global examination of the form: the US Holocaust Memorial Museum in Washington, DC; the House of Terror in Budapest; the Kigali Genocide Memorial Centre in Rwanda; the Museum of Memory and Human Rights in Santiago, Chile; and the National September 11 Memorial Museum in New York. Together, these case studies illustrate the historical emergence and global spread of the memorial museum and show how this new cultural form of commemoration is intended to be used in contemporary societies around the world emerging from widely divergent forms of political violence.